Budaya Organisasi Dan Kinerja Guru: Peran Moderasi Politik Organisasi - ., Herizon; Syahsudarmi, Siti; Nasution, Imran AI Ucok (CV. ITTC INDONESIA, 2025)
The study was conducted in all junior high schools in Singingi sub-district with the aim of organizational political perception in moderating the influence of organizational culture on teacher performance. The population of this study was 120 people. Based on this population size, according to the Krejcie and Morgan (1970) table, the sample size for this study was 92 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that organizational culture is positively related to teacher performance; organizational politics moderates the relationship between organizational culture and teacher performance. this shows that the level of influence of organizational culture on teacher performance can change depending on the political dynamics in the organization